The Matching Effect of Destinations’ Crisis Communication - Zhang, Jiangchi; Xie, Chaowu; Chen, Yanying; Dai, You-De; Yi-Jun, Wang (Journal of travel research, 2023)
The match between destinations’ crisis communication sources and crisis types, and their impacts on tourists’ travel intentions, has not yet been investigated. This research explored the effect of destinations’ crisis communication on tourists’ travel intentions based on different crisis types (i.e., victimized and preventable crises) and communication sources (i.e., from the government, businesses, and other tourists). Results showed that crisis type had a matching effect on the impact process of crisis communication sources on tourists’ travel intentions. In addition, the mediation effects of tourists’ heuristic processing and perceived safety on destinations’ crisis communication–tourists’ travel intentions were confirmed. This study uncovered a matching effect of destinations’ crisis communication sources and crisis types. Results offer valuable theoretical and practical implications regarding destinations’ crisis communication agendas, crisis communication systems, and strategies for alleviating negative consequences of crises.